Hubungan Faktor Keturunan Dengan Kanker Payudara DI RSUD Abdoel Moeloek - Ariq Naufal Azmi; Bambang Kurniawan; Andi Siswandi; Ade Utia Detty (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Cancer is one of the uncontagious diseases that become a matter of public health, breast cancer can be sporadic, familial, and hereditary. Objectives: To find out if there is a history factor relationship of heredity with breast cancer in the Dr. Abdul Moeloek Hospital. Observational analytic research with cross-sectional approaches. The sample in this study is that all breast cancer patients recorded in 2019 medical records were taken in total sampling. Analysis of data using univariate analysis and bivariate analysis using Chi-Square. Results: Known frequency distributions of hereditary history in breast cancer patients most with a family history of breast cancer amounted to 61.0%. There is known a significant link between the hereditary history factor and breast cancer (p-value: 0.000; 0R: 10.9)